Analysis of the Effectiveness of Restaurant Tax Revenue in Labuhan Ratu District, Bandar Lampung - Azka, Mauzatie; Yuliawan, Dedy (Lafadz Jaya Publisher, 2024)
This research aims to find out how big the contribution of restaurant taxes is and the extent of the effectiveness of restaurant taxes in Labuhan Ratu District in Bandar Lampung City. This research was conducted in Labuhan Ratu District, specifically at restaurants in Labuhan Ratu District using BPPRD data from Bandar Lampung City. The research results show that the average contribution of restaurant taxes to Bandar Lampung City Regional Original Income for the 2019-2022 period is 0.25% - 0.28% per year. This figure shows that the contribution of restaurant taxes to Original Regional Income is still very poor and the level of effectiveness of the management of restaurant tax collection in Bandar Lampung City during the 2019-2022 period can be said to be effective, with an average level of effectiveness of 84.03%. The higher the effectiveness ratio, the better the restaurant tax collection.